BLOCKCHAIN ACCEPTANCE ANALYSIS USING THE UTAUT2 MODEL - Indrawati, Indrawati; Firdaus, Nanda Wahyu (TRIKONOMIKA, 2022)
MSME is the primary driver of the Indonesian economic sector, which, unfortunately, remains struggling in controlling and adopting technology, including Blockchain technology. Blockchain is an effective technology that includes all business activities processes and improves the performance and security of company data. This study explored behavioral intervention in adopting the Blockchain technology in MSME Phil’s Auto, Kinandara Boutique, Sabana Restaurant, and Narassi Coffee. The analysis performed in this study was qualitative data analysis on interview results with the MSMEs’ owners. The study results show that the four MSMEs are interested and willing to implement Blockchain technology. Blockchain is expected to help the company improve business activity effectiveness and company data security. Future studies are expected to provide solutions to MSME problems in adopting Blockchain technology.